PENGELOLAAN PEMBELAJARAN TEMATIK Dl KELAS 1 RSDBI PURWOREJO TAHUN PELAJARAN 2011/2012 - Atik Sumiyati; Sutama Sutama; Suyatmini Suyatmini (Universitas Muhammadiyah Surakarta, 2012)
The study was aimed at describing the thematic teaching and learning management in first Grade at RSDBI Purworejo Academic Year of 2011/2012. This is qualitative research. Data collection technique used was observation, interview, and documentation. The research results are as follows: (1) In the planning activity includes identification of basic competency of mapping activities. The mapping activity is conducted to obtain a thorough and complete all the standards of competence, basic competence and indicators of the subjects that combined. The second stage is the determination of the adjusted standard theme and basic competencies in the subjects taught. The next stage is creating a theme network based on basic competencies and indicators of the subjects taught. The final stage is planningg the syllabus and lesson plans. (2) The implementation of thematic leaning proceeds through three stages: introduction, implementation and evaluation activity. (3) Evaluation of thematic leaning was performed three times: in the beginning of the course, during the course, and at the end of the course. The evaluation was carried out in oral and written activities. Evaluation in writing (normative evaluation) assessed students’ attitudes and actions after joining the teaching and leaning process in the classroom.